Anmeldelser - Møller Sørensen, Søren (Danish Yearbook of Musicology, 2010)
Review of: Peter Kivy: Antithetical Arts. On the Ancient Quarrel Between Literature and Music. Oxford: Clarendon Press / Oxford University Press, 2009.